Case Report: Life-threatening Kasabach–Merritt phenomenon in a 2-month-old child - Wong Grossman, Ashley V.; Forero, Juan Pablo; Yu, Jeffrey S.; Gilbert, Megan M.; Anand, Kanwaljeet J. S. (Frontiers in Pediatrics, 2025)
We present a rare case of a 2-month-old girl, born at term, who was admitted to the pediatric intensive care unit for fussiness, increasing abdominal distension, and intermittent diarrhea for one week. She was found to be hypertensive, coagulopathic, and suffering from unrelenting ascites. Over the course of the following month, her symptoms became life-threatening, and she was intubated, sedated, and paralyzed. She underwent multiple diagnostic and therapeutic procedures, including exploratory laparotomy, MRI, colonoscopy, and multiple peritoneal drains. After several weeks, the medical teams reached a consensus diagnosis of a rare and complex vascular anomaly characterized by a life-threatening Kasabach–Merritt Phenomenon (KMP). KMP is known to occur in association with several anomalies, including kaposiform hemangioendothelioma and kaposiform lymphangiomatosis. Life-saving therapies were initiated, including methylprednisolone and sirolimus. The patient was ultimately discharged and sent home with her parents. To our knowledge, this is the only reported case describing this constellation of symptoms in a critically ill infant. Multidisciplinary cooperation was key in saving the patient's life. Critical care providers should consider vascular anomalies in patients with similar presentations.